Frontiers in imaging magnetism with polarized x-rays - Fischer, Peter (Frontiers in Physics, 2015)
Although magnetic imaging with polarized x-rays is a rather young scientific discipline, the various types of established x-ray microscopes have already taken an important role in state-of-the-art characterization of the properties and behavior of spin textures in advanced materials. The opportunities ahead will be to obtain in a unique way indispensable multidimensional information of the structure, dynamics and composition of scientifically interesting and technologically relevant magnetic materials.